Porcine recombinant factor VIII: an additional weapon to handle anti-factor VIII antibodies - Mannucci, Pier Mannuccio (Blood Transfus, 2017)
This review focuses on the use of recombinant porcine factor VIII (FVIII) for the treatment of bleeding episodes in patients with severe haemophilia A complicated by inhibitors and in those with acquired haemophilia A due to the onset of anti-FVIII autoantibodies. We present the main characteristics of recombinant porcine factor VIII (FVIII) and provide a summary of the published results of the clinical studies of this novel recombinant FVIII. There is a special emphasis on how the use of recombinant porcine factor VIII (FVIII) is expected to improve the clinical management of these patients.